Implications Of Family Type On Work-Family Balance And Quality Of Life: A Cross Sectional Study - John Lalmuanawma; Dr. H.Elizabeth (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Work-family balance is an important concept and a global phenomenon in our contemporary world. There are various factors which has implications on the dynamics of work-family balance and quality of life. Meanwhile, family environment is considered as one of the main contributing factors to work-family balance. In addition, there are also several studies which confirmed the inter-correlation of work-family balance and quality of life. It is crucial to meet work-family balance for a better quality of life and vice versa. Indeed, the modern urban lifestyle and work environment of employees has resulted in encountering the importance of a healthy work-family balance. For an individual employee to meet a productive work-family balance, there are major initiatives which could be introduced at the family level such as spousal support and other family members. The employees in different sectors are performing multiple tasks and have to commit on their work beyond the stipulated time and many of them have to bring home their unfinished tasks which brought psychological distress and work-family imbalance to the employees’ family life. Thus, it affects their professional growth and job performances. Therefore, the article present the implications of family type on work-family balance and quality of life across three different sectors such as hospital settings, banking sectors and educational institutions